Surveying by occultations - Akilit, Noe B. (1962)
The method of surveying by occulation can be adopted in connecting systesm of triangulation which are too far apart to be connected by the conventional method. this involves the prediction of the time and date a satr will be occulted by the moon, and in what portion of the earth will the occulatation be visible; the observation of the time of the occultation; and finally the reduction of the data obtained.